Time course of adipose tissue dysfunction associated with antioxidant defense, inflammatory cytokines and oxidative stress in dyslipemic insulin resistant rats. Issue 4 (13th March 2015) - D'Alessandro, María Eugenia; Selenscig, Dante; Illesca, Paola; Chicco, Adriana; Lombardo, Yolanda B.
Abstract : Time course of adipose tissue dysfunction in dyslipemic insulin resistant rats. Abstract : The dysfunctional adipose tissue of rats fed a sucrose-rich diet was investigated following the time course of the development of oxidative stress, changes in proinflammatory cytokines and adiponectin levels, and their relationship with insulin resistance. We analyzed the morphometric characteristics of epididymal adipocytes, de novo lipogenesis enzyme activities and cellular antioxidant defense, inflammatory mediators, adiponectin levels and insulin resistance in rats fed a sucrose-rich diet for 3, 15 or 30 weeks and compared to those fed a control diet. The results showed a depletion of antioxidant enzyme activities in the fat pads of rats fed a sucrose-rich diet, with an increase in xanthine oxidase activity and lipid peroxidation after 3, 15 and 30 weeks on the diet. Superoxide dismutase activity and the redox state of glutathione showed a significant decrease at weeks 15 and 30. This was accompanied by visceral adiposity and enhanced lipogenic enzyme activities. An increase in the plasma levels of proinflammatory markers (TNF-α and IL-6) was recorded only after 30 weeks on the diet. A reduction in plasma adiponectin levels accompanied the time course of deterioration of whole-body insulin sensitivity. The results suggest that lipid peroxidation, depletion of antioxidant defenses and changes in inflammatory cytokines induced by a sucrose-rich diet contribute to the dysregulation of adipose tissue and insulin resistance. Finally, these results show that the progressive deterioration of adipose tissue function, which begins in the absence of both visceral adiposity and overweight, is highly dependent on the length of time on the diet.